2019
DOI: 10.1007/s13205-019-1766-9
|View full text |Cite
|
Sign up to set email alerts
|

An overview of cephalosporin antibiotics as emerging contaminants: a serious environmental concern

Abstract: Antibiotics have been categorized as emerging pollutants due to their indiscriminate usage, continuous input and persistence in various environmental matrices even at lower concentrations. Cephalosporins are the broad-spectrum antibiotics of β-lactam family. Owing to its enormous production and consumption, it is reported as the second most prescribed antibiotic classes in Europe. The cephalosporin wastewater contains toxic organic compounds, inorganic salts, and active pharmaceutical ingredients (API) which p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 106 publications
(122 reference statements)
1
30
0
1
Order By: Relevance
“…Briefly, the results showed that all synthesized derivatives have log P values <5, low tendency to be absorbed through the gastrointestinal tract, optimal TPSA values (in the range of 180-212 Å 2 ), low number of violations of Lipinki's rule of five, [40] and they do not cross the blood-brain barrier. It is important to note that Lipinski's rules represent statistical guidelines for orally administered drugs, and there are numerous cases of orally available drugs that do not comply with all the rules, for example, cefozopran (Firstcin®) as a representative of cephalosporin [41] and azithromycin [42] and roxithromycin [43] as representatives of other well-known antibacterial F I G U R E 4 Pharmacophore (red), antipharmacophore (blue), and ballast (gray) parts of the derivatives 10b (left) and 10n (right) drugs. Moreover, clinically used drugs are subjected to metabolism in vivo, which increases the degradation of the molecule into the various fragments and increases polarity for excretion.…”
Section: Absorption Distribution Metabolic Liability Prediction and Excretion Studiesmentioning
confidence: 99%
“…Briefly, the results showed that all synthesized derivatives have log P values <5, low tendency to be absorbed through the gastrointestinal tract, optimal TPSA values (in the range of 180-212 Å 2 ), low number of violations of Lipinki's rule of five, [40] and they do not cross the blood-brain barrier. It is important to note that Lipinski's rules represent statistical guidelines for orally administered drugs, and there are numerous cases of orally available drugs that do not comply with all the rules, for example, cefozopran (Firstcin®) as a representative of cephalosporin [41] and azithromycin [42] and roxithromycin [43] as representatives of other well-known antibacterial F I G U R E 4 Pharmacophore (red), antipharmacophore (blue), and ballast (gray) parts of the derivatives 10b (left) and 10n (right) drugs. Moreover, clinically used drugs are subjected to metabolism in vivo, which increases the degradation of the molecule into the various fragments and increases polarity for excretion.…”
Section: Absorption Distribution Metabolic Liability Prediction and Excretion Studiesmentioning
confidence: 99%
“…Cephalosporins are a class of antibiotics frequently prescribed, grouped into five generations based on their spectrum [ 5 , 6 , 7 ]. Second generation cephalosporins have a relatively broad spectrum activity, a variety of methods of administration and are often prescribed to treat respiratory infections [ 6 , 8 , 9 ], urinary tract infections, soft tissue infections and for surgical prophylaxis [ 5 , 8 , 9 , 10 ]. Cephalosporins prescribed by age groups showed higher prescribing rates for the adult population (18–64 years old) (n = 32,828), followed by those under 18 years old (n = 15,169), while the elderly population had lower prescribing rates (n = 7016) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics including cephalosporins have active pharmaceutical ingredients (API) that have a harmful impact on the environment. It acts as a emerging contaminants (Das et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, The duration and severity of exposure of antibiotic like, ceftriaxone have a signi cant effect on bla CTX-M resistance gene ampli cation in the gut ora and it leads antibiotic antibiotic resistance, which is the major causes signi cant health care hazards (Sileshi et al 2016); (Meletiadis et al 2017). Cephalosporrin antibiotic contamination has a strong negative impact on human health and ecosystem as it waste water contain toxic substances (Das et al 2019). This pollution has an effect on marine ecosystems, halting ecosystem and organism functions during their life cycle (Kraemer et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation